Using space syntax method and GIS-based analysis for the spatial allocation of roadside rest areas - Zaleckis, Kęstutis; Kamičaitytė-Virbašienė, Jūratė; Matijošaitienė, Irina (Transport, 2015)
A well-grounded system of Roadside Rest Areas (RRA) for transit travellers and local inhabitants in Latvia and Lithuania is absent. To select places for the location of RRA on Latvian–Lithuanian cross-border roads space syntax method and GIS-based analysis was used. The aim of this article is to present the developed methodology, results of the performed research and to lead discussion for the further development and applicability of the methodology. The application of space syntax method to nine transit roads in Latvian–Lithuanian border zone reveals that considering both local and regional contexts three roads or their parts could be recommended for the location of RRA. For the more precise location of RRA GIS-based method was developed. This method includes the GIS capabilities of information collection, spatial analysis and multi-criteria (eight criteria were selected) evaluation. The main proposed methodical stages are: creation of the thematic GIS database; formulation of RRA sites selection criteria, division of the analysed road into intervals, and assignment of attribute data according to the criteria to the road intervals; generation of buffer zones for the analysed road and evaluation of them according the selected criteria; assignment of values provided to the buffer zones to the road intervals attribute data and total rating of roadside area potential to equip rest areas; elaboration of road buffer zone area suitable for the location of RRA.